Risk of postmenopausal hormone therapy and patient history factors for the survival rate in women with endometrial carcinoma - Hein, Alexander; Schneider, Michael; Renner, Stefan; Fasching, Peter; Fießler, Cornelia; Titz, Susanna; Hartmann, Arndt; Beckmann, Matthias; Thiel, Falk C. (Archives of Gynecology and Obstetrics, 2019)
Purpose: Postmenopausal hormone therapy (HT) is known to affect the development of hormone-dependent endometrial carcinoma (type I EC). Several studies on breast and ovarian carcinoma have shown that HT influences the molecular profile and prognostic behavior of these tumors. This study aimed to investigate the influence of prior HT and other risk factors on the prognosis in a cohort of patients with invasive endometrial carcinoma (EC). Methods: Among 525 patients diagnosed with EC between 1987 and 2010, 426 postmenopausal patients were identified. Information regarding HT was available in 287 of these patients, 78 of whom had a history of HT and 209 of whom did not. Both overall survival (OS) and progression-free survival (PFS) were analyzed. In addition to OS and PFS, risk factors such as age at diagnosis, postmenopausal HT, body mass index (BMI), diabetes mellitus, tumor stage, EC type (I or II), and recurrences were analyzed. Results: Relative to HT alone, women with EC and a history of HT had a longer survival than those with no HT. However, the Cox proportional hazards model showed that it was not HT itself, but rather other characteristics in the HT group that were causally associated with longer survival. Conclusions: Age (the older, the worse) and tumor stage (the higher, the worse) were significant influences on overall survival. Patients with HT also had lower BMIs, less diabetes, more type I EC, and fewer recurrences in comparison with the non-HT group. With regard to the PFS, it made no difference whether the patient was receiving HT.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Endometrial carcinoma; Estrogen; Hormone replacement therapy; Hormone therapy; Overall survival; Progesterone; Prognosis; Risk factors